Female Fire-Setters: Gender-Associated Psychological and Psychopathological Features. Issue 4 (1st October 2016) - Alleyne, Emma; Gannon, Theresa A.; Mozova, Katarina; Page, Thomas E.; Ó Ciardha, Caoilte
Abstract : Objective : Female fire-setters are reported to commit nearly one-third of deliberately set fires, yet there are limited studies examining the characteristics that distinguish them from suitable comparison groups. The aim of this study is to compare incarcerated female fire-setters with incarcerated male fire-setters and female offender controls on psychopathological and psychological features that could be targeted via therapeutic interventions. Method : We recruited 65 female fire-setters, 128 male fire-setters, and 63 female offenders from the prison estate. Participants completed a battery of validated tools assessing psychiatric traits and psychological characteristics (i.e., inappropriate fire interest, emotion/self-regulation, social competence, self-concept, offense-supportive attitudes, and boredom proneness) highlighted in the existing literature. Results : Major depression and an internal locus of control distinguished female fire-setters from male fire-setters. Alcohol dependence, serious/problematic fire interest, and more effective anger regulation distinguished female fire-setters from the female offender control group. Conclusions : This is the first study to examine differences between female fire-setters, male fire-setters, and female control offenders on both psychopathological features and psychological traits. These findings highlight the gender-specific and offense-specific needs of female fire-setters that clinicians need to consider when implementing programs that ensure client responsivity.